Associação entre características sociodemográficas, nível e tipo de atividade física no tempo de lazer, função laboral, desequilíbrio de torques musculares - Orlandi Junior, Oliveira (2023)
During fires or in situations of rescue and victim transport, the ability to generate power is crucial for firefighters. In these events, the tasks performed can lead to significant overload, fatigue, injuries, and musculoskeletal pains (MSP). Although asymmetric muscle forces have been associated with various occupational activities and pathological conditions, these relationships are not clear in firefighters. Therefore, the aim of this study is to analyze the incidence of MSP in firefighters associated with sócio-demographic characteristics, physical activity profile, job function, muscle force imbalance, and musculoskeletal pain. The study has a cross-sectional design. The sample consisted of 41 military firefighters of both sexes from the administrative (n=17) and operational (n=24) sectors. A questionnaire (IPAQ) was administered with questions related to personal information, physical activity during a normal week, job function: type, time in the role, time spent in sitting and standing positions per day. Questions about MSP history (location and intensity) were asked using the Corlett diagram. Isometric torque tests – peak torque (PT) and torque development rate (TD) – were also performed on the flexor and extensor muscles of the trunk, lower limbs, upper limbs, and bilaterally (right and left). Descriptive analysis, decision tree, and linear regression were used in the statistical analysis. The research identified 40 firefighters with at least one site of pain, with the highest prevalence of pain in the back (75%), cervical region (51%), knee (41%), and shoulder (39%). Torque imbalances showed no correlation with MSP. Age, body mass index, and exercise practice had no relation to MSP. Operational service firefighters had lower PT and TD of trunk muscles and higher MSP in the lower back compared to administrative firefighters. An inverse association was found between MSP of trunk flexor muscles and PT normalized by body mass and TD (R2 = 0.552). An inverse association occurred between TD of extensors and normalized PT of elbow flexors and pain in the upper limbs (R2= 0.458). There was an inverse relationship between MSP of the lower limbs and TD of hip flexor torque (R2= 0.549). These findings can be powerful predictors of MSP, thus assisting in improving the health of firefighters and directing physical training programs for this population.